A traditional hip implant is as effective as newer types for people over 65. (2nd July 2019) - Cook, Rob; Lamont, Tara; Martin, Rosie
The study: Fawsitt C, Thom H, Hunt L. Choice of prosthetic implant combinations in total hip replacement: cost-effectiveness analysis using UK and Swedish hip joint registries data. Value Health 2019;22:303-12. This study was funded by the NIHR Research for Patient Benefit Programme (project number PB-PG-0613-31032). To read the full NIHR Signal, go to https://discover.dc.nihr.ac.uk/content/signal-000771/a-traditional-hip-implant-is-as-effective-as-more-expensive-newer-types-for-older-people